2017
DOI: 10.1155/2017/8196256
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic Fibrin Clot Phenotype in Patients with Deep Vein Thrombosis and Pulmonary Embolism: A New Risk Factor for Recurrence

Abstract: Prothrombotic fibrin clot phenotype, involving faster formation of dense meshwork composed of thinner and highly branched fibers that are relatively resistant to plasmin-induced lysis, has been reported in patients with not only myocardial infarction or stroke, but also venous thromboembolism (VTE), encompassing deep vein thrombosis (DVT), and/or pulmonary embolism (PE). Prothrombotic fibrin clot phenotype, in particular prolonged clot lysis time, is considered a novel risk factor for VTE as well as venous thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 88 publications
(120 reference statements)
2
27
0
Order By: Relevance
“…Previous studies have linked fibrin structure to fibrinolytic properties. Clots that are structurally denser and stiffer have an increased resistance to fibrinolysis compared with softer clots, and slower degradation rates have been associated with an increased risk of thrombotic events . Not surprisingly, our results show that neonatal fibrin clots formed immediately after CPB without the influence of other therapies had a significantly faster degradation rate compared with all other groups.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have linked fibrin structure to fibrinolytic properties. Clots that are structurally denser and stiffer have an increased resistance to fibrinolysis compared with softer clots, and slower degradation rates have been associated with an increased risk of thrombotic events . Not surprisingly, our results show that neonatal fibrin clots formed immediately after CPB without the influence of other therapies had a significantly faster degradation rate compared with all other groups.…”
Section: Discussionmentioning
confidence: 51%
“…It should be underscored that with the increase in compact, highly branched networks with thin fibers significantly correlated with cirrhosis severity. Clots composed of thin fibers and small pores have been suggested to be more thrombogenic [42,46,47], but the mechanisms underlying the formation of these prothrombotic fibrin clots have not yet been described. Our in vitro experiments revealed that oxidative stress is a strong determinant of these evident clot structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…The role of clot structure and function for prognostic markers in venous thromboembolic disorders specifically is described in another review article. 53 Fibrin clot permeability has also been shown to be a good predictor of stroke and bleeding in anticoagulated patients with atrial fibrillation. 54 Patients clots that had lower Ks were at increased risk of stroke or transient ischemic attack and major bleeds.…”
Section: Structural Clot Changes and Thrombotic Outcomesmentioning
confidence: 99%